Responsible communication in digital infographics published by pharmaceutical companies - Rivera Salas, Paola Eunice (2020)
Organizations currently use infographics on social media to have a greater impact on audiences. Objective: Characterize the presence of Responsible Communication in infographics published by pharmaceutical companies on the social network Facebook. Methodology: Quantitative, descriptive, transversal, and non-experimental. The variable of interest was Responsible Communication (CR) in two subfields: Corporate Communication and Digital Communication (Hernández-Flores, 2018). 69 infographics published by 4 multinational pharmaceutical companies that had an official website in said network in 2018 were observed. Results: As for Digital Communication, infographics are an effective communication tool; although, the interactivity that arises from said publication is not attended by the observed companies. On Corporate Communication, corporate culture is promoted in infographics, but not the reputation of the companies analyzed. Conclusions: It is a priority to detect the areas of opportunity that organizations must execute a CR towards their audiences using digital tools.